2011
DOI: 10.1002/ejoc.201101045
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of DNA Conjugates by Strain‐Promoted Azide–Cyclooctyne Cycloaddition in the Solid Phase

Abstract: Conjugation of ligands to DNA oligonucleotides has been achieved in the solid phase by strain-promoted azide-alkyne cycloaddition (SPAAC). The oligonucleotide, modified with a simple nonfluroinated, monocyclic octyne, efficiently forms conjugates with a range of azide dipoles with varying steric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…39,40 The fluorescein azide 21 was selected to demonstrate the potential of SPAAC for introduction of fluorescent tags. Having previously demonstrated that 21 required post-synthetic conjugation to DNA, 32 the same strategy was adopted for RNA-cyclooctyne 12. Thus, 12 (0.025 μmol, 1 eq., 200 μM), obtained from 7 following cleavage from the resin and deprotection, was exposed to a solution of 21 (40 eq.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 The fluorescein azide 21 was selected to demonstrate the potential of SPAAC for introduction of fluorescent tags. Having previously demonstrated that 21 required post-synthetic conjugation to DNA, 32 the same strategy was adopted for RNA-cyclooctyne 12. Thus, 12 (0.025 μmol, 1 eq., 200 μM), obtained from 7 following cleavage from the resin and deprotection, was exposed to a solution of 21 (40 eq.)…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 7 was treated with biotinyl- (19), 32 cholesteryl-(20) 32 or fluoresceinyl- (21) 32 azides in both aqueous and non-aqueous media at room temperature. Conjugation to the biotinyl azide (19), furnished 23c after 4 h in 90% (v/v) aqueous DMSO, whilst DCM was the solvent of choice for cholesteryl conjugation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing number of examples of building blocks for DNA and RNA functionalized with ring‐strained conjugation partners. Heaney et al reported the use of the resin‐supported conjugation method for postsynthetic modification of DNA at the 5′‐end of oligonucleotides (Scheme ) 46. They efficiently conjugated a simple nonfluorinated, monocyclic octyne (building block 17 ) that reacts with a range of azide dipoles with varying steric and electronic characteristics.…”
Section: Strain‐promoted Azide–alkyne Cycloaddition (Spaac)mentioning
confidence: 99%
“…[2k-2m] In addition, catalyst-free routes to triazole-linked cholesterol-oligonucleotide conjugates have been reported. [3] However, aside from exploitation of the masked functionality of the isoxazole nucleus to access polyhydroxylated steroids, cholesterol conjugates with this heterocyclic linker are relatively unknown. Thermally promoted cycloadditions to C-17-anchored steroidal alkynes have yielded important reaction intermediates.…”
Section: Introductionmentioning
confidence: 99%